CFD Modeling of Trickle-Bed Reactors for Catalytic Hydropurification Processes - HU, CHEE KIONG (Universiti Teknologi PETRONAS, 2016)
In trickle-bed reactors (TBRs), gas and liquid reactants flow co-currently downward through a packed bed solid catalysts. TBRs are applied intensively in industrial catalytic hydropurification processes, due to low energy dissipation rate and high catalyst loading per unit volume of the liquid. Understanding the operation behaviors of TBRs influenced by hydrodynamic parameters fluctuation such as gas holdup, liquid holdup, wetting efficiency of the catalyst particles, and gas and liquid flow rates is important for the design of industrial TBRs and evaluation of the reactor performance. Due to the complexity of the two-phase fluid interaction in TBR, a thorough understanding of hydrodynamics in industrial TBR under actual operating conditions has not been achieved. Conventional studies carried out through experimental and empirical methods are limited to analysis of pilot plant TBR.